2014
DOI: 10.7567/apex.7.085001
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the electron transport properties of a single 〈110〉 InAs nanowire

Abstract: InAs nanowire with 〈110〉 orientation is proposed for use as an electron spin transport channel for application to spintronics devices, particularly the Datta–Das spin transistor. Stable zinc blende crystal NWs were grown using a molecular beam epitaxy system. Subsequently, global back-gate NW field effect transistors were fabricated, and the superiority of the electrical transport properties within our resultant 〈110〉 NWs was demonstrated by comparing the field-effect mobility with a 〈111〉 NW control sample. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Using the sheet resistance Rs from the VDP measurements, the electron Hall mobility was obtained through l H ¼ 1 qR S n S resulting in l H ¼ 5400 cm 2 /V s. In comparison, a detailed study on Hall measurements on h111i oriented InAs NWs with diameters larger than 160 nm was recently reported. 19 These NWs contained a high density of stacking faults similar to the devices fabricated here, and exhibited a mobility of l H ¼ 3120 cm 2 /V s. An investigation of h110i oriented InAs NWs with diameters larger than 440 nm was reported by Cui et al 20 who found l H > 8000 cm 2 /V s, attributing the high mobility to the pure zinc-blende crystal structure. Measurements on planar, 50 lm wide and 20 nm thick InAs Hall structures with (100) surface orientation 21 resulted in l H ¼ 7000 cm 2 /V s while films affected by dislocations resulted in a significantly reduced mobility of l H $ 2000 cm 2 /V s. The comparatively high mobility value measured here for a thin InAs crossbar (95 Â 23 nm 2 ) which also includes stacking faults thus strongly suggests the absence of dislocations, as such defects clearly are most detrimental to the mobility.…”
supporting
confidence: 73%
“…Using the sheet resistance Rs from the VDP measurements, the electron Hall mobility was obtained through l H ¼ 1 qR S n S resulting in l H ¼ 5400 cm 2 /V s. In comparison, a detailed study on Hall measurements on h111i oriented InAs NWs with diameters larger than 160 nm was recently reported. 19 These NWs contained a high density of stacking faults similar to the devices fabricated here, and exhibited a mobility of l H ¼ 3120 cm 2 /V s. An investigation of h110i oriented InAs NWs with diameters larger than 440 nm was reported by Cui et al 20 who found l H > 8000 cm 2 /V s, attributing the high mobility to the pure zinc-blende crystal structure. Measurements on planar, 50 lm wide and 20 nm thick InAs Hall structures with (100) surface orientation 21 resulted in l H ¼ 7000 cm 2 /V s while films affected by dislocations resulted in a significantly reduced mobility of l H $ 2000 cm 2 /V s. The comparatively high mobility value measured here for a thin InAs crossbar (95 Â 23 nm 2 ) which also includes stacking faults thus strongly suggests the absence of dislocations, as such defects clearly are most detrimental to the mobility.…”
supporting
confidence: 73%
“…A hole mobility of 48 ± 12 cm 2 V –1 s –1 was also extracted for the p-doped sample. These carrier mobilities are low in comparison to an undoped reference, yet could be improved through modulation doping. ,, More importantly, we have demonstrated an increase in photoconductivity lifetime in comparison to an undoped reference. The photoconductivity lifetime was found to be 3.8 ± 0.1 ns for n-type doping and 2.5 ± 0.02 ns for p-type doping.…”
Section: Discussionmentioning
confidence: 78%
“…An n-type conductivity in GaAs nanowires has however been achieved through Te core doping, yet as Te is a high vapor pressure element, its use in high-mobility molecular beam epitaxy (MBE) chambers is not ideal. , Alternatively, a shell of doped semiconductor may be grown over a nominally undoped NW core. This “shell doping” technique has allowed many doped semiconductor heterostructures to be realized. More recently, modulation doping has also been achieved in GaAs/AlGaAs core–shell heterostructures. These structures have been shown to possess both high mobilities and long carrier lifetimes, yet relatively low carrier concentrations .…”
mentioning
confidence: 99%
“…On the other hand, the relation between the orientations and electrical transport properties of InAs NWs has not been experimentally clarified to date. Differences on electron mobility (μ e ) have been observed experimentally between ⟨011⟩ and ⟨111⟩ oriented zinc-blende (ZB) InAs NWs, and the lower mobility in ⟨111⟩ oriented ZB InAs NWs has been attributed to the high density of stacking faults in that work. However, to our best knowledge, rare experimental work has been reported regarding the electrical transport properties of InAs NWs with the growth direction apart from the ZB ⟨011⟩ and ⟨111⟩.…”
mentioning
confidence: 82%